Volatility Regimes in Central and Eastern European Countries? Exchange Rates - Michael Frömmel (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
The choice of an exchange rate arrangement affects the volatility of the exchange rate: higher flexibility goes ahead with increasing volatility and vice versa (Flood and Rose 1995, 1999). We investigate the exchange rate volatility of six Central and Eastern European countries (CEEC) between 1994 and 2004. The analysis merges two approaches, the GARCH-model (Bollerslev 1986) and the Markov Switching Model (Hamilton 1989). We discover switches between high and low volatility regimes which are consistent with policy settings for Hungary, Poland and, less pronounced, the Czech Republic, whereas Romania and Slovakia do not show a clear picture. Slovenia, finally, shows some kind of anticipation of the wide fluctuation margins in ERM2.
Keywords: F36; F31; E42; 330; CEEC; exchange rate volatility; regime switching GARCH; Markov switching model; transition economies